PERAN RADIOGRAFER DALAM PENANGGULANGAN PENYEBARAN COVID-19 - Prahardi; Syaifudin Ramadhan Hidayat (Perhimpunan Radiografer Indonesia (PARI), 2021)
ABSTRACT Background: Radiographers as part of health workers have a big role in handling COVID-19 during the pandemic. Radiographers not only play an important role in making good diagnostic images, but also in efforts to prevent the transmission of COVID-19 infection. Radiographers can take many roles in preventing the spread of COVID-19, including providing education about health protocols to patients and families and disinfecting workspaces and equipment. However, this role is often overlooked by radiographers Methods: This type of research is descriptive analytic which describes the actual situation of the respondent who is the object of research. The data was obtained from the survey results which were then processed using the cross sectional study method Results: The results of a survey of 22 radiographers who work in the Banyumas area, only 42.9% always ask the patient or patient's family to wash their hands before entering the examination room, 33.3% sometimes ask to wash their hands while 23.8% do not ask or suggest to wash hands when entering the examination room. In terms of disinfection of equipment and workspaces, there were 4.7% of radographers who never carried out disinfection, 28.6% occasionally carried out disinfection and 66.7% who always carried out disinfection. Conclusions: Radiographers have an important role in preventing the spread of COVID-19. There are still many radiographers who do not play an important role in preventing the spread of COVID-19. It is necessary to raise awareness to radiographers besides they have the main task of making radiographs or therapy for patients properly and correctly, they also have an important role in overcoming the spread of covid-19